2018
DOI: 10.1016/j.pediatrneurol.2018.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor Function in Individuals With Rett Syndrome

Abstract: BACKGROUND: Individuals with Rett syndrome (RTT) are notoriously reliant on the use of eye gaze as a primary means of communication. Underlying an ability to communicate successfully via eye gaze is a complex matrix of requirements, with an intact oculomotor system being just one element. To date, the underlying neural and motor pathways associated with eye gaze are relatively under-researched in RTT. PURPOSE: This study was undertaken to plug this gap in knowledge and to further the understanding of RTT in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Few studies have investigated ocular findings in patients with this syndrome, and those reports which have studied eye abnormalities found that refractive errors and gaze tracking were the main areas of concern. 4 , 5 , 6 , 7 JOAG has not been studied as a finding in Rett Syndrome, nor has there been any literature describing any type of glaucoma in patients with this condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have investigated ocular findings in patients with this syndrome, and those reports which have studied eye abnormalities found that refractive errors and gaze tracking were the main areas of concern. 4 , 5 , 6 , 7 JOAG has not been studied as a finding in Rett Syndrome, nor has there been any literature describing any type of glaucoma in patients with this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Townend et al also studied the oculomotor function of 18 girls with Rett syndrome, and their work suggests that this function remains intact in Rett syndrome patients. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Various defects have been observed in RTT patients and Mecp2 null mice, but so far few have been reported to have ocular defects in RTT patients (Jain et al 2010 ; Townend et al 2018 ; de Breet et al 2019 ). This study detailed MeCP2 expression in the retina and analyzed structural changes including ganglion cell morphology in the retina of Mecp2 KO.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TCF4 is highly expressed in the adult hippocampal dentate gyrus, one of the few brain regions where neural stem/progenitor cells generate new functional neurons throughout life. Scientists also assayed whether histone deacetylase (HDAC) inhibition would be sufficient to normalize the enhanced hippocampal long-term potentiation (LTP) phenotype [ 311 ]. Surprisingly, treatment with the HDAC inhibitor trichostatin resulted in significantly reduced LTP in the Tcf4 +/− mouse hippocampus.…”
Section: Transcriptional Deregulationmentioning
confidence: 99%